Corticostriatal cocaine-seeking ensembles are defined by differing gene expression from sucrose-seeking ensembles using a within-subject dual self-administration and seeking mouse model - Litif, Carl G. (2025)
Recurrent cocaine seeking is a hallmark of cocaine use disorder. To develop therapeutic targets, it is critical to understand the neurobiological changes specific to cocaine-seeking in context with the seeking of non-drug rewards, e.g., sucrose. The nucleus accumbens (NAc) and medial prefrontal cortex (mPFC) are known regions associated with cocaine- and sucrose-seeking ensembles, i.e., a sparse population of co-activated neurons linked with behavior. Within ensembles, transcriptomic alterations in the NAc and mPFC underlie the learning and recall of cocaine- and sucrose-seeking behavior. However, the transcriptomics exclusively driving cocaine seeking independent from sucrose seeking have not yet been defined using a within-subject approach. Using Ai14:cFos-TRAP2 transgenic mice in a dual cocaine and sucrose self-administration model, we fluorescently sorted and characterized the transcriptomes defining cocaine-seeking in reference to the sucrose-seeking ensemble, overlapping ensemble in between cocaine and sucrose-seeking, and the non-ensemble population. Our data suggests there are robust transcriptomic changes linked with cocaine-seeking that differ from sucroseseeking ensembles and the non-ensemble population which could guide future studies aimed to detangle cocaineseeking behavior without altering non-drug reward seeking.